Interdependent Utilities, Charity, and Pareto Optimality: Comment - Danielsen, Albert L. (Quarterly Journal of Economics, 1975)
I. The Schall model, 478. — II. Interdependent utilities and the Edgeworth box, 479. — Conclusion, 480.